Peran Brand Image Sebagai Variabel Intervening Pada Produk Pocari - Astuti, Nur Andri Fitri Widi; Soepatini, Soepatini (Pascasarjana STIE Amkop Makassar, 2024)
This research seeks to examine how product quality and promotion influence repurchase intention, with brand image serving as an intervening factor specifically for Pocari products. The study employs a quantitative method, utilizing probability sampling through purposive sampling technique. Primary data collection involves distributing closed questionnaires via Google Forms, utilizing the Likert scale.Primary data is acquired firsthand from participants through the distribution of questionnaires to gather information. The study's population consisted of 153 consumers of Pocari Sweet. PLS-SEM technique is employed to forecast and examine intricate models with less stringent data requirements. The data analysis method in this research utilizes PLS with the assistance of SMARTPLS Software. The findings of this investigation suggest that brand image acts as a mediator in the connection between product quality and promotion's influence on Repurchase Intention.